Traditional Chinese medicine treatment selection for straightened cervical curvature and therapeutic observation - Wang, Gang; Long, Xiang-yu (Journal of acupuncture and tuina science, 2017)
Objective To observe the clinical efficacy of different therapies in treating straightened cervical curvature. Methods A hundred patients with straightened cervical curvature were randomized into 5 groups to receive corresponding treatment. The clinical efficacies and the changes of cervical curvature in the five groups were compared. Results Different therapies all produced certain effectiveness in treating cervical spondylosis patients. The total effective rates in the acupuncture group and tuina group were both 100%, and the rates in the traction group, oral medication group and Chinese medicinal application group were all lower than the rates in the acupuncture group and tuina group ( P <0.05). It was shown that the more significant the change of cervical curvature, the more significant the clinical efficacy. Conclusion Correcting the straightened cervical curvature is a way to swiftly release pain brought by cervical spondylosis; the optimization of different therapies ensures the achievement of long-term effectiveness; acupuncture and tuina are both effective in restoring the cervical curvature.